Automate Employees Effiiency Gauging and Task Scheduling - Purushothman P; Piriyangan K; Sasini Nuwanthika (International Journal of Engineering and Management Research, 2022)
There is a common fact in the world that all employees and employers are not satisfied with themselves. This is due to a lack of awareness about the work done by employees. But most of the time employees put their maximum effort into their work and didn’t get recognized by the employer. As a result, the challenge is identifying the efficiency of the employees and managing their respective schedules of tasks. This paper proposes an approach to help employers identify the employees’ efficiency in an urgent situation. Also, this approach can help to manage the work allocation by their efficiency to the respective tasks. This paper will discuss how it could be used in real-time scenarios autonomously. This paper presents a practical method for modeling and solving a dynamic resource allocation of automatic scheduling problem using a forward gauging heuristic approach in the case of an Organization employee’s Project and task respective scheduling.